Digital Transformation in Rural Areas: Directions for Digital Village Development in Developing Countries - Ikbal, Muhammad; Erfina, Erfina; Lawelai, Herman; Lubis, Sandi; Darlis, Muhammad Akbar Ali (JPSI (Journal of Public Sector Innovations), 2025)
This research investigates the development of digital villages in developing countries, focusing on the challenges and opportunities in implementing Information and Communication Technology (ICT) to improve the quality of life and socio-economic conditions in rural areas. The objectives of this study include identifying the key challenges and opportunities in digital village development, exploring how ICT can enhance rural livelihoods, and proposing a model for effective, innovative technology implementation in rural settings. A systematic literature review was conducted, analyzing 867 articles from the Scopus database between 2015 and 2025. The RStudio application was used to analyze the data and visualize publication trends, collaboration patterns, and key themes related to digital village development. The findings highlight that while digital villages can potentially reduce the rural-urban divide, challenges such as insufficient digital infrastructure, low digital literacy, and limited government policies hinder progress. However, successful cases like China’s Digital Village initiatives demonstrate that ICT-driven innovation can drive substantial improvements in rural areas with supportive government policies and active community participation. This study contributes to the existing literature by emphasizing the integration of social, cultural, and economic factors in adopting digital technologies and by promoting sustainable innovation ecosystems that empower rural communities. Limitations include focusing on a few developing countries and relying on published articles, which may not fully capture the nuances of rural technology implementation in resource-constrained environments. Future research should include case studies from diverse regions and examine the role of government policies in accelerating the adoption of digital village models. This research recommends a more inclusive and innovation-oriented approach to digital village development, incorporating technological infrastructure and the empowerment of local communities through digital literacy programs and public-private sector collaboration.